A conservation of resources view of personal engagement in the development of innovative behavior and work-family conflict. Issue 6 (3rd October 2016) - Chen, Yu-Shan; Huang, Stanley Y.J.
Abstract : Purpose: The purpose of this paper is to examine how personal engagement (PE) may be related with work-family conflict (WFC) and innovative behavior (IB) at the same time. Design/methodology/approach: This study tested the proposed model using a longitudinal data with 1, 501 employees from R&D departments in information technology industry of Greater China at multiple points (Time 1 to Time 3) in time over a ten-month period. Findings: This study exhibits how charismatic leadership style, colleague support (CS), and self-esteem (SE) are capable of predicting the PE, which, in turn, positively related to the IB and the WFC. Research limitations/implications: The present study proposed a model of the PE, but there are other variables that might also be important for the PE. Practical implications: These finding suggests that managers not only must inspire and enable employees to apply their full energy to their work (e.g. PE), but must also alleviate the WFC. Originality/value: The study drawn from Kahn's (1990) engagement theory and conservation of resources view to explain how the leadership style, CS, and SE can increase PE, which, in turn, increase positive organization behavior (IB) and negative organization behavior (WFC) at the same time.